Peningkatan Pengetahuan Penyakit Tidak Menular sebagai Langkah Preventif Hipertensi dan Diabetes Mellitus - Nika Nur Safitri; Aufanissa Luzida Azmi Aurelia; Widya Putri Pangestu; Ajeng Tri Isna; Rohman Abdullah; Muhammad Farhan Fadilah; Yusinta Eka Sari; Dian Yosi Arinawati (Fakultas Kedokteran Gigi, Universitas Jember, 2024)
The prevalence of non-communicable diseases (PTM) in Indonesia is very high. Types of non-communicable diseases that many people in Indonesia experience include hypertension and diabetes mellitus. In Sleman Regency, hypertension and diabetes mellitus occupy the top two rankings of the types of diseases that many outpatients suffer from at the puskesmas. The findings in Dusun Ngemplaksari that many people, especially the elderly, have diabetes mellitus and hypertension. The high number of people suffering from this non-communicable disease is not accompanied by changes in healthy lifestyles in the community. The purpose of this community service is to provide education and examinations related to hypertension and diabetes mellitus to the people of Ngemplaksari Hamlet. This activity is carried out with socialization and a physical examination, including checking blood pressure, blood sugar, height, weight, and abdominal circumference, which is also followed by anamnesis before the examination is carried out. The results of the counseling show that there is an increase in the knowledge of the Ngemplaksari Hamlet community about non-communicable diseases; this can be seen from the increase in the pretest and posttest scores of the Ngemplaksari hamlet community. Increased awareness can also be seen from health cadres who took the initiative to learn how to use the GCU rapid test tool so that they can carry out examinations on the Ngemplaksari Hamlet community both independently and in collaboration with competent parties. This examination and education regarding PTM have had a big positive impact on the community by increasing the awareness and knowledge of the people of Ngemplaksari Hamlet regarding steps to prevent and treat non-communicable diseases.Keywords: Diabetes; Education; Hypertension; Non-communicable diseases